Open Access 2020 – The final road to Open Access - Geschuhn, Kai; Schlachter, Michael (Septentrio Conference Series, 2016)
Open Access 2020 is an international initiative that aims to induce the swift, smooth and scholarly-oriented transformation of today’s scholarly journals from subscription to open access publishing on a large scale. The last decades of the open access movement have made open access become strong as a principal- but weak in practice. With OA2020 we aim to move the focus to a new concrete goal: converting the default business model of scholarly publishing from subscription to open access. The poster outlines backgrounds as well as a roadmap of the initiative.